Ceramic heat sink material and preparation method thereof

By using Si-Al alloy ingots, porous C-Si3N4 and sintering aids, dense AlN-SiC ceramic material was prepared, which solved the problem of low thermal conductivity of SiC-AlN composite ceramics in the prior art, and achieved high thermal conductivity and suitable ceramic heat sink materials.

CN119613122APending Publication Date: 2025-03-14DONGGUAN PEPPER GRAY TECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202411903886.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, when preparing SiC-AlN composite ceramics, the sintering temperature is high and it is difficult to get dense, and AlN is prone to hydrolysis and oxidation, resulting in the thermal conductivity of the finished product being much lower than the theoretical value.

Method used

Si-Al alloy ingot, porous C-Si3N4 and sintering aid are used as raw materials, and AlN-SiC ceramic material with uniform phase distribution and dense phase distribution is formed through pre-sintering and discharge plasma sintering.

Benefits of technology

It improves the thermal conductivity of ceramic heat sink materials, has large grains and small grain boundaries, and is suitable for heat sink ceramic substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613122A_ABST
    Figure CN119613122A_ABST
Patent Text Reader

Abstract

The invention discloses a ceramic heat sink material and a preparation method thereof, and the preparation method comprises the following steps: S1, taking a Si-Al alloy ingot, porous C-Si3N4 and a sintering aid as raw materials, and carrying out pre-sintering to obtain a compound; and S2, carrying out spark plasma sintering treatment on the compound in a vacuum atmosphere to obtain the ceramic heat sink material, according to the preparation method, the Si-Al alloy ingot and the porous C-Si3N4 are taken as raw materials, the Si-Al alloy ingot permeates into the porous C-Si3N4 material under the heating melting condition, the composite AlN-SiC ceramic material which is uniform in phase distribution and compact is formed in situ in combination with the sintering aid, the obtained ceramic heat sink material is large in crystal grain and small in number of crystal boundaries, scattering of phonons is reduced during heat conduction, and the heat sink material has the advantages of being high in heat sink efficiency and good in heat sink performance. The heat conductivity is improved; meanwhile, the prepared ceramic heat sink material is high in grain density and uniformity, low in oxygen content in crystal lattices and moderate in impurity-phase silicon content, so that the heat conductivity is high, and the ceramic heat sink material is suitable for being used as a heat sink ceramic substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of heat sink materials, and in particular to a ceramic heat sink material and a preparation method thereof. Background Art

[0002] In the field of electronic engineering, heat sinks are classified as "passive heat dissipation elements". They are made of metal, non-metal or composite materials with good thermal conductivity, light weight and easy processing, attached to the heat-generating surface, and transfer heat to fluid media such as air, liquid coolant or an additional radiator in a complex heat exchange mode.

[0003] In recent years, compared with other substrate materials, ceramic substrate materials have become one of the best choices for heat sink substrates due to their outstanding thermal conductivity. AlN ceramics and SiC ceramics are important advanced ceramic materials. Compared with Al2O3, AlN has better thermal conductivity, good insulation and low dielectric constant. In addition, SiC has the characteristics of high thermal conductivity, high hardness, good wear resistance and corrosion resistance, excellent thermal shock resistance and low thermal expansion coefficient. SiC-AlN composite ceramics can not only make up for the shortcomings of the two existing alone, but also maintain the original excellent properties. At the same time, because the two have similar density and thermal expansion coefficient, the composite ceramic products have high density, high thermal conductivity and good bending strength. However, the raw materials used in the preparation of SiC-AlN composite ceramics in related technologies are often directly compounded with SiC and AlN. During the preparation process, SiC has a strong covalent bond, which makes the sintering temperature of the ceramic high and difficult to densify, while AlN is easily hydrolyzed and oxidized, and the lattice oxygen content in the finished product is high. As a result, the thermal conductivity of the prepared SiC-AlN composite ceramics is much lower than the theoretical thermal conductivity of AlN ceramics and SiC ceramics.

[0004] Therefore, it is necessary to provide a solution for improving the thermal conductivity of SiC-AlN composite ceramic materials to further meet the requirements of SiC-AlN composite ceramic materials as heat sink substrate materials. Summary of the invention

[0005] In view of the defects in the prior art, the present invention proposes a ceramic heat sink material and a preparation method thereof, which are used to solve the problem of how to improve the thermal conductivity of SiC-AlN ceramic heat sink materials.

[0006] In order to solve the above technical problems, this application provides the following technical solutions.

[0007] In a first aspect, the present application provides a method for preparing a ceramic heat sink material, comprising the following steps: S1. Pre-sintering Si-Al alloy ingot, porous C-Si3N4 and sintering aid as raw materials to obtain a composite; S2. Under vacuum atmosphere, the composite is subjected to spark plasma sintering treatment to obtain a ceramic heat sink material.

[0008] Preferably, the sintering aid includes one or more of MgSiN2 and Ti.

[0009] Preferably, the preparation method of porous C-Si3N4 is as follows: α-Si3N4 with a particle size of 0.3-0.5µm, carbon black with a particle size of 10-20nm, phenolic resin, and a dispersant are mixed and dispersed in anhydrous ethanol, and then a binder and a plasticizer are added to continue ball milling to obtain a slurry; the slurry is heated and cured at 140-160°C, and then pyrolyzed at 1000-1200°C under an inert atmosphere to obtain C-Si3N4; wherein the mass ratio of α-Si3N4 to carbon black is 20:8-10.

[0010] Preferably, in the Si-Al alloy ingot, Si accounts for 55-65% and Al accounts for 35-45%.

[0011] Preferably, the molar ratio of Si-Al alloy ingot to porous C-Si3N4 is 4-5:1 based on the molar ratio of Al to N.

[0012] Preferably, the molar ratio of the sintering aid to the Si-Al alloy ingot is 1-2:10.

[0013] Preferably, the pre-sintering temperature is 1000-1400° C., and the heating program is 5-10° C. / min.

[0014] Preferably, the spark plasma sintering temperature is 1500-1900° C., and the temperature rise program is 10-30° C. / min.

[0015] In a second aspect, the present application provides a ceramic heat sink material.

[0016] In a third aspect, the present application provides an application of a ceramic heat sink material in the field of heat sink substrates.

[0017] In summary, compared with the prior art, the present invention achieves the following technical effects: The present application uses Si-Al alloy ingots and porous C-Si3N4 as raw materials. Under heating and melting conditions, the Si-Al alloy ingots are infiltrated into the porous C-Si3N4 material, and combined with a sintering aid, an in-situ composite AlN-SiC ceramic material with uniform phase distribution and density is formed. The resulting ceramic heat sink material has large grains and a small number of grain boundaries. The scattering of phonons during heat conduction will also be reduced, thereby improving thermal conductivity. At the same time, the prepared ceramic heat sink material has high grain density and uniformity, low oxygen content in the lattice and moderate content of impure silicon, thereby having high thermal conductivity and is suitable for use as a heat sink ceramic substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 It is the SEM image of porous C-Si3N4; Figure 2 This is the SEM image of the ceramic heat sink material prepared in Example 1. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0021] The present application provides a method for preparing a ceramic heat sink material, comprising the following steps: S1. Pre-sintering Si-Al alloy ingot, porous C-Si3N4 and sintering aid as raw materials to obtain a composite; S2. Under vacuum atmosphere, the composite is subjected to spark plasma sintering treatment to obtain a ceramic heat sink material.

[0022] The present invention uses Si-Al alloy ingot and porous C-Si3N4 as raw materials. Under heating and melting conditions, the Si-Al alloy ingot infiltrates into the porous C-Si3N4 material, and combines with sintering aids to form in situ a composite AlN-SiC ceramic material with uniform phase distribution and compactness. The reaction mechanism is as follows: 4Al(l) + Si3N4(s) → 4AlN(s) + 3Si(s) Si(l) + C(s) → SiC ( s ) AlN-SiC ceramic material and residual Si impurity phase are obtained through the above reaction; in the present application, the residual Si exists in the form of liquid phase in the final stage of melt infiltration, which provides more "free space" for the grain growth of SiC and AlN particles, forms AlN-SiC ceramics with larger grain size, reduces grain boundary phonon scattering, and is beneficial to the improvement of thermal conductivity, but too much residual Si will not only increase the melting temperature, but also increase the heterogeneous interface at the grain boundary, hinder the heat transfer of phonons, and reduce the thermal conductivity; on the other hand, since Al and Si in Si-Al alloy have a strong affinity for O, the Si-Al alloy will inevitably undergo surface oxidation to form Al2O3 and SiO2, resulting in the formation of an Al-O inhibition interface layer even when the AlN-SiC ceramic material is synthesized under a vacuum state, thereby reducing the thermal conductivity.

[0023] In order to resolve the above contradiction, the present application adopts the method of adding sintering aids, reacting the sintering aids with oxygen in the lattice to generate a second phase, purifying the lattice, and at the same time utilizing the sintering aids to consume a portion of the excess residual Si, so that the content of residual Si is within the range of 1-5wt% of the overall ceramic material, thereby improving the thermal conductivity; on the other hand, the addition of sintering aids is also beneficial in lowering the sintering temperature, thereby obtaining a ceramic material with a larger grain size, thereby improving the thermal conductivity of the material.

[0024] Furthermore, the present application adopts a two-step calcination method to prepare ceramic materials to improve thermal conductivity. The advantage of spark plasma sintering is that the sintering temperature is low, which is conducive to the formation of large grains, but the sintering time of spark plasma sintering is short, and pores are easily formed between particles during the sintering process. In the present application, the porosity is reduced by pre-sintering, and a large number of sintering necks are promoted to form between particles, which accelerates the atomic diffusion between particles. In the subsequent spark plasma sintering stage, it is beneficial to improve the densification degree of ceramic materials and the interfacial bonding strength between particles, thereby improving thermal conductivity; furthermore, the present application uses Si-Al alloy ingots with a smaller surface area than Si-Al alloy powders, which overcomes the excessive oxidation of Si-Al alloys in the preparation of AlN-SiC ceramics and reduces the formation of Al-O inhibition interface layers.

[0025] In some embodiments, the sintering aid includes one or more of MgSiN2 and Ti.

[0026] In the present application, MgSiN2 is used as an oxygen-free additive, which can reduce the lattice oxygen content compared to sintering additives with high oxygen content, thereby significantly improving the thermal conductivity of AlN-SiC ceramics; metal titanium powder reacts with Si to generate TiSi2, which can reduce the content of residual impurity Si and improve the thermal conductivity of the material.

[0027] In some embodiments, the preparation method of porous C-Si3N4 is as follows: α-Si3N4 with a particle size of 0.3-0.5µm, carbon black with a particle size of 10-20nm, phenolic resin, and a dispersant are mixed and dispersed in anhydrous ethanol, and then a binder and a plasticizer are added to continue ball milling to obtain a slurry; the slurry is heated and cured at 140-160°C, and then pyrolyzed at 1000-1200°C under an inert atmosphere to obtain C-Si3N4; wherein the mass ratio of α-Si3N4 to carbon black is 20:8-10.

[0028] In this embodiment, the binder includes but is not limited to one or more of polyvinyl pyrrolidone and polyvinyl alcohol, the plasticizer includes but is not limited to one or more of diisobutyl phthalate and dioctyl phthalate, the dispersant includes but is not limited to one or more of camellia oil polyol and diisostearyl malate, and the role of the binder and plasticizer is to improve the compatibility of α-Si3N4 with carbon black and phenolic resin; the pore size of the porous C-Si3N4 obtained by the above process is 0.1-0.4µm. The present application controls the ratio of α-Si3N4 to carbon black to control the ratio of C to Si in C-Si3N4, thereby achieving control of the content of impure phase Si in the final ceramic material.

[0029] In some embodiments, in the Si-Al alloy ingot, Si accounts for 55-65% and Al accounts for 35-45%.

[0030] In this embodiment, if the proportion of silicon is too high, the melting temperature of the pretreatment is high, which is not conducive to the formation of large grains, and thus is not conducive to improving the thermal conductivity of the ceramic material. If the proportion of silicon is too low, the effect of reducing the phonon scattering of the grain boundaries decreases, which also leads to a decrease in thermal conductivity. The Si-Al alloy ingot is obtained in a conventional manner by a person skilled in the art: silicon material is added to molten aluminum liquid by mass for smelting, and then alloyed at a temperature greater than 1000°C, and then cooled in a mold.

[0031] In some embodiments, the molar ratio of Si-Al alloy ingot to porous C-Si3N4 is 4-5:1 based on the molar ratio of Al to N.

[0032] In some embodiments, the molar ratio of the sintering aid to the Si—Al alloy ingot is 1-2:10.

[0033] In this embodiment, if the sintering aid is too high, the Si impurity phase will be consumed too much, and if the sintering aid is too low, the amount of Si impurity phase consumed will be reduced, both of which are not conducive to improving the thermal conductivity.

[0034] In some embodiments, the pre-sintering temperature is 1000-1400° C., and the temperature ramp is 5-10° C. / min.

[0035] Preferably, the pre-sintering temperature is 1000-1200° C., and the temperature rise program is 5-8° C. / min. The present application can achieve pre-sintering at low temperature by using raw material ratio.

[0036] In some embodiments, the spark plasma sintering temperature is 1500-1900° C., and the temperature ramp is 10-30° C. / min.

[0037] Preferably, the spark plasma sintering temperature is 1500-1600° C., and the temperature rise program is 20-30° C. / min. Spark plasma sintering at this temperature is conducive to forming large-grained composite AlN-SiC ceramic materials and improving the thermal conductivity of the materials.

[0038] The present application provides a ceramic heat sink material, which is an AlN-SiC composite ceramic containing residual silicon or silicon-containing compounds (TiSi2), with low oxygen content in the lattice, moderate content of heterogeneous silicon (1-2%), and large grains (95-105nm). The ceramic heat sink material prepared by the present application has large grains and a small number of grain boundaries, and the scattering of phonons during heat conduction will also be reduced, thereby improving thermal conductivity; the ceramic heat sink material prepared by the present application has high grain density and uniformity, low oxygen content in the lattice and moderate content of heterogeneous silicon, so it has high thermal conductivity and is suitable for use as a heat sink ceramic substrate.

[0039] The present application provides an application of a ceramic heat sink material in the field of heat sink substrates.

[0040] The present solution is further described below through specific embodiments.

[0041] Raw material preparation The preparation method of porous C-Si3N4 is as follows: 20g of α-Si3N4 with a particle size of 0.4µm, 8g of carbon black with a particle size of 20nm, 15g of phenolic resin, and 1g of camellia oil polyol are mixed and dispersed in 50g of anhydrous ethanol, and ball milled for 6h, and then 5g of polyvinyl pyrrolidone and 5g of diisobutyl phthalate are added and ball milled for 24h to obtain slurry; the slurry is heated and cured at 150℃ for 30min, and then pyrolyzed at 1100℃ under argon atmosphere to obtain C-Si3N4. Its SEM image is shown as follows Figure 1 As shown; the pore distribution of the obtained C-Si3N4 measured by mercury intrusion method is between 0.1-0.4µm.

[0042] Example 1 A method for preparing a ceramic heat sink material comprises the following steps: S1. Under a vacuum degree of 1 Pa, 4 mol of Si-Al alloy ingot (Si 60wt%, Al 40wt%), 1 mol of porous C-Si3N4, 0.5 mol of MgSiN2, and 0.5 mol of Ti powder were mixed, heated to 1000°C at a rate of 5 min / °C, and pre-sintered to obtain a composite; S2. Under the condition of a vacuum degree of 1 Pa, the composite is subjected to spark plasma sintering at a rate of 30°C / min to 1500°C for 2 hours to obtain a ceramic heat sink material.

[0043] Example 2 A method for preparing a ceramic heat sink material comprises the following steps: S1. Under a vacuum degree of 1 Pa, 4 mol of Si-Al alloy ingot (Si 60wt%, Al 40wt%), 1 mol of porous C-Si3N4, 0.5 mol of MgSiN2, and 0.5 mol of Ti powder were mixed, heated to 1000°C at a rate of 5 min / °C, and pre-sintered to obtain a composite; S2. Under the condition of a vacuum degree of 1 Pa, the composite is subjected to spark plasma sintering at a rate of 40°C / min to 1500°C for 2 hours to obtain a ceramic heat sink material.

[0044] Example 3 A method for preparing a ceramic heat sink material comprises the following steps: S1. Under a vacuum degree of 1 Pa, 6 mol of Si-Al alloy ingot (Si 60wt%, Al 40wt%), 1 mol of porous C-Si3N4, 0.5 mol of MgSiN2, and 0.5 mol of Ti powder were mixed, heated to 1000°C at a rate of 5 min / °C, and pre-sintered to obtain a composite; S2. Under the condition of a vacuum degree of 1 Pa, the composite is subjected to spark plasma sintering at a rate of 30°C / min to 1500°C for 2 hours to obtain a ceramic heat sink material.

[0045] Example 4 A method for preparing a ceramic heat sink material comprises the following steps: S1. Under a vacuum degree of 1 Pa, 4 mol of Si-Al alloy ingot (Si 60wt%, Al 40wt%), 1 mol of porous C-Si3N4, 2 mol of MgSiN2, and 2 mol of Ti powder were mixed, heated to 1000°C at a rate of 5 min / °C, and pre-sintered to obtain a composite; S2. Under the condition of a vacuum degree of 1 Pa, the composite is subjected to spark plasma sintering at a rate of 30°C / min to 1500°C for 2 hours to obtain a ceramic heat sink material.

[0046] Example 5 A method for preparing a ceramic heat sink material comprises the following steps: S1. Under a vacuum degree of 1 Pa, 4 mol of Si-Al alloy ingot (Si 60wt%, Al 40wt%), 1 mol of porous C-Si3N4, 0.2 mol of MgSiN2, and 0.2 mol of Ti powder were mixed, heated to 1000°C at a rate of 5 min / °C, and pre-sintered to obtain a composite; S2. Under the condition of a vacuum degree of 1 Pa, the composite is subjected to spark plasma sintering at a rate of 30°C / min to 1500°C for 2 hours to obtain a ceramic heat sink material.

[0047] Example 6 A method for preparing a ceramic heat sink material comprises the following steps: S1. Under a vacuum degree of 1 Pa, 4 mol of Si-Al alloy ingot (Si 70wt%, Al 30wt%), 1 mol of porous C-Si3N4, 0.5 mol of MgSiN2, and 0.5 mol of Ti powder were mixed, heated to 1000°C at a rate of 5 min / °C, and pre-sintered to obtain a composite; S2. Under the condition of a vacuum degree of 1 Pa, the composite is subjected to spark plasma sintering at a rate of 30°C / min to 1500°C for 2 hours to obtain a ceramic heat sink material.

[0048] Example 7 A method for preparing a ceramic heat sink material comprises the following steps: S1. Under a vacuum degree of 1 Pa, 4 mol of Si-Al alloy ingot (Si 60wt%, Al 40wt%), 1 mol of porous C-Si3N4, and 1 mol of Y2O3 were mixed, heated to 1000°C at a rate of 5 min / °C, and pre-sintered to obtain a composite; S2. Under the condition of a vacuum degree of 1 Pa, the composite is subjected to spark plasma sintering at a rate of 30°C / min to 1500°C for 2 hours to obtain a ceramic heat sink material.

[0049] Comparative Example 1 A method for preparing a ceramic heat sink material comprises the following steps: S1. Under a vacuum degree of 1 Pa, 4 mol of Si-Al alloy ingot (Si 60wt%, Al 40wt%) and 1 mol of porous C-Si3N4 were mixed, heated to 1000°C at a rate of 5 min / °C, and pre-sintered to obtain a composite; S2. Under the condition of a vacuum degree of 1 Pa, the composite is subjected to spark plasma sintering at a rate of 30°C / min to 1500°C for 2 hours to obtain a ceramic heat sink material.

[0050] Comparative Example 2 A method for preparing a ceramic heat sink material comprises the following steps: S1. Under a vacuum degree of 1 Pa, 2 molAlN, 2 molSiC, 0.5 mol MgSiN2, and 0.5 mol Ti powder were mixed, heated to 1000 ° C at a rate of 5 min / ° C, and pre-sintered to obtain a composite; S2. Under the condition of a vacuum degree of 1 Pa, the composite is subjected to spark plasma sintering at a rate of 30°C / min to 1500°C for 2 hours to obtain a ceramic heat sink material.

[0051] Comparative Example 3 A method for preparing a ceramic heat sink material comprises the following steps: S1. Under the condition of vacuum degree of 1Pa, 4mol Si-Al alloy ingot (Si 60wt%, Al 40wt%), 1mol porous C-Si3N4, 0.5mol MgSiN2, and 0.5mol Ti powder were mixed, and the temperature was raised to 1500℃ at a rate of 30℃ / min, and the composite was spark plasma sintered for 2h to obtain a ceramic heat sink material.

[0052] Comparative Example 4 A method for preparing a ceramic heat sink material comprises the following steps: S1. Under a vacuum degree of 1 Pa, 4 mol of Si-Al alloy ingot (Si 60wt%, Al 40wt%), 1 mol of porous C-Si3N4, 0.5 mol of MgSiN2, and 0.5 mol of Ti powder were mixed, heated to 1000°C at a rate of 5 min / °C, and pre-sintered to obtain a composite; S2. Under the condition of a vacuum degree of 1 Pa, the temperature is raised to 1800° C. at a rate of 30° C. / min and the composite is subjected to spark plasma sintering for 2 h to obtain a ceramic heat sink material.

[0053] Comparative Example 5 A method for preparing a ceramic heat sink material comprises the following steps: S1. Under a vacuum degree of 1 Pa, 4 mol of Si-Al alloy powder (Si 60wt%, Al 40wt%), 1 mol of porous C-Si3N4, 0.5 mol of MgSiN2, and 0.5 mol of Ti powder were mixed, heated to 1000°C at a rate of 5 min / °C, and pre-sintered to obtain a composite; S2. Under the condition of a vacuum degree of 1 Pa, the composite is subjected to spark plasma sintering at a rate of 30°C / min to 1500°C for 2 hours to obtain a ceramic heat sink material.

[0054] Test and Evaluation The performance of the ceramic heat sink materials obtained from different embodiments and comparative examples was tested. The results are shown in Table 1. The test items include: Average grain size: The grain size of different ceramic heat sink materials can be obtained through XRD testing; Lattice oxygen content: The lattice oxygen content in different ceramic heat sink materials was tested using the inert melt infrared absorption method; Content of impure Si phase: XRD test can be used to obtain the mass percentage of pure Si impure phase in different ceramic heat sink materials.

[0055] Thermal conductivity: The thermal conductivity of different ceramic heat sink materials is tested in accordance with the national standard GB / T 39862-2021.

[0056] Table 1 Performance test results of different ceramic heat sink materials

[0057] As can be seen from Table 1, compared with Example 1, Example 2 accelerates the heating rate of spark plasma sintering, the grain size becomes smaller, and the thermal conductivity decreases; Compared with Example 1, Example 3 increases the amount of Si-Al alloy ingot, increases the lattice oxygen content, increases the content of heterophase Si, and decreases the thermal conductivity; Compared with Example 1, Example 4 increases the amount of sintering aid, reduces the lattice oxygen content, and reduces the content of heterophase Si, but the thermal conductivity does not change much. The possible reason is that the presence of a large amount of sintering aid also has a certain negative impact on the thermal conductivity; Compared with Example 1, Example 5 reduces the amount of sintering aid, increases the lattice oxygen content, increases the content of heterophase Si, and decreases the thermal conductivity; Compared with Example 1, Example 6 adjusts the Si / Al ratio in the raw material, reduces the grain size, increases the lattice oxygen content, increases the content of heterophase S i content increases, thermal conductivity decreases; Example 7 changes the type of sintering aid relative to Example 1, the lattice oxygen content increases, the impurity Si content increases, and the thermal conductivity decreases; Comparative Example 1 does not use sintering aids relative to Example 1, the grains become smaller, the lattice oxygen content is high, the impurity Si content is high, and the thermal conductivity decreases; Comparative Example 2 replaces the preparation raw materials relative to Example 1, the grains become smaller, the lattice oxygen content is high, the impurity Si content is high, and the thermal conductivity decreases; Comparative Example 3 removes the pre-sintering step relative to Example 1, the grains become smaller, the lattice oxygen content is high, and the thermal conductivity decreases; Comparative Example 4 increases the final sintering temperature relative to Example 1, and the thermal conductivity does not change much; Comparative Example 5 replaces the Si-Al alloy ingot with Si-Al alloy powder relative to Example 1, the lattice oxygen content increases, and the thermal conductivity decreases.

[0058] Figure 2 This is the SEM image of the ceramic material obtained in Example 1 of the present application. Figure 2 It can be seen that the microstructures prepared in the present application are all very dense, without obvious pores, indicating that AlN and SiC are evenly distributed, while the Si impurity phase and the Si-containing compound impurity phase appear white.

[0059] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a ceramic heat sink material, characterized in that: The steps include: S1. Pre-sintering Si-Al alloy ingot, porous C-Si3N4 and sintering aid as raw materials to obtain a composite; S2. Under vacuum atmosphere, the composite is subjected to spark plasma sintering treatment to obtain the ceramic heat sink material.

2. The method for preparing a ceramic heat sink material according to claim 1, characterized in that: The sintering aid includes one or more of MgSiN2 and Ti.

3. The method for preparing a ceramic heat sink material according to claim 1, characterized in that: The preparation method of the porous C-Si3N4 is as follows: α-Si3N4 with a particle size of 0.3-0.5µm, carbon black with a particle size of 10-20nm, phenolic resin, and a dispersant are mixed and dispersed in anhydrous ethanol, and after ball milling, a binder and a plasticizer are added to continue ball milling to obtain a slurry; the slurry is heated and cured at 140-160°C, and then pyrolyzed at 1000-1200°C under an inert atmosphere to obtain the C-Si3N4; wherein the mass ratio of α-Si3N4 to carbon black is 20:8-10.

4. The method for preparing a ceramic heat sink material according to claim 1, characterized in that: In the Si-Al alloy ingot, Si accounts for 55-65% and Al accounts for 35-45%.

5. The method for preparing a ceramic heat sink material according to claim 1, characterized in that: Calculated by the molar ratio of Al to N, the molar ratio of Si-Al alloy ingot to porous C-Si3N4 is 4-5:

1.

6. The method for preparing a ceramic heat sink material according to claim 1, characterized in that: The molar ratio of the sintering aid to the Si-Al alloy ingot is 1-2:

10.

7. The method for preparing a ceramic heat sink material according to claim 1, characterized in that: The pre-sintering temperature is 1000-1400°C, and the heating program is 5-10°C / min.

8. The method for preparing a ceramic heat sink material according to claim 1, characterized in that: The temperature of spark plasma sintering is 1500-1900°C, and the heating program is 10-30°C / min.

9. A ceramic heat sink material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the ceramic heat sink material according to claim 9 in the field of heat sink substrates.

Citation Information

Patent Citations

  • Method for preparing AlN-SiC composite ceramic by promoting reactive infiltration through oxygen uptake diversion layer

    CN118515487A

  • Method for preparing high thermal conduction silicon nitride ceramic with magnesium silicon nitride as sintering aid

    CN1654427A

  • Porous body with coating film, method for manufacturing the same, and joined body

    JP2011037645A

Cited By

  • Method for preparing AlN-SiC composite ceramic by promoting reactive infiltration through oxygen uptake diversion layer

    CN118515487A

  • High-thermal-conductivity black aluminum nitride ceramic substrate and preparation method and application thereof

    CN122608426A